The impact of organizational culture on the emergence of informal organization in the organization: Case study of the Algerian Company for Industrial Equipment and Machinery ALEMO - djemoui, fatimazohra (Finance and Business Economies Review, 2023)
This study aims to highlight the reality of informal organization in light of the prevailing organizational culture in the organization, where groupings and relationships arise within the formal organization to alleviate the pressures of the latter. In order to reveal the reality of the impact of organizational culture on the emergence and spread of informal organization, a questionnaire was prepared for a sample of workers (75 workers) in the Algerian Company for Industrial Equipment and Machinery ALEMO in Oued Hmeimim El Kharoub, Constantine Province. Where we reached a set of results, the most important of which are: the existence of an average level of organizational culture at the level of the Algerian Company for Industrial Equipment and Machinery ALEMO, and an average level of informal organization, with a direct correlation between the two variables.